Solution Suggestions for Medical Malpractice Claims - Aşırdizer, Mahmut; Ekiz, Aykut (The Bulletin of Legal Medicine, 2022)
While it is hoped that medical practice errors will be minimized in parallel with the development and widespread use in science and technology; the increasing number of lawsuits filed for unfair medical malpractice claims and the amount of compensation paid leads to the development of defensive medicine. Consequently, physicians’ defensive behaviour models such as using radiological methods such as unnecessary MRI, CT, x-ray, ultrasonography and mammography, unnecessary hospitalization of the patient, unnecessary tests, unnecessary consultations, unnecessary biopsy, unnecessary consultations, unnecessary cesarean section and unnecessary drug prescribing are developing. In addition, it is observed that physician candidates with higher success they avoid branches which have more medical malpractice claims, but that are vital to human life. In this study, in order to prevent defensive medical behaviors and to protect physicians from unfair medical malpractice claims, the literature including the discussions made especially in the United States of America was reviewed, and in the light of these, solution proposals were defined by taking into account the facts of our country.